The Information Technology for Remote and Virtual Practical Researches on Robotics - Sukhoruchkina, O.N.; Progonnyi, N.V. (Кибернетика и вычислительная техника, 2019)
The purpose of the article is to consider the information technology capabilities in the organization of remote access to physical equipment and virtual means for practical research and training on robotics. Methods. Methods of distributed information and computing processes, communication protocols, and web application programming are used. Results. Two types of specialized means of our laboratory complex — physical equipment with remote access and virtual environments are considered. The general structures of autonomous mobile robot and sensor module that can be used remotely for certain research and practical training are presented. Some examples of web applications that are intended to familiarize students with certain types of robotics systems by their 3D models and to perform corresponding practical tasks with the automatic results checking are shown.